The First Three Months Of Quality Of Life Of Older Person With Hip Fracture - Wantonoro Wantonoro; Edy Suprayitno; Sugiyarto Sugiyarto; Heru Susanto (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Hip fracture increased due to the aging phenomenon. Hip fracture injuries are identified as one of the most serious healthcare problems affecting the elderly, including instrument and physical function and quality of life problem.This study aimed to evaluate quality of life between 1st and 3rd months older person with hip fracture who had received surgical treatment. A prospective study design with 66 older people who have hip surgical treatment. Face-to-face Quality of life assessment used SF36 instrument was conducted. In general, a significant difference between 1st and 3rd months post hospital discharge was found (p = 0.001). In addition, the role of disability due to emotional problems and role disability due to physical health problems has the highest in differences than another dimension (M ± SD; 55.0 ± 38.6 and M ± SD; 44.3 ± 38.7; respectively), However, there is no significant difference in fatigue subscale (p = 0.624) between 1st and 3rd months post hospital discharge. In general, there was an increase in the quality of life between 1st  and 3rd months among hip elderly patients without concomitant disease. Comprehensive nursing care is needed in order to maintain and improve all dimensions of the quality of life for elderly with hip surgery. Longitudinal studies with a complexity of variables and a larger number of samples are highly recommended for future study.